Intraspecific Variation of Edwardsiella anguillarum From Non‐Anguillid Fish From Varied Geographic Origins - Abigail R. Armwood; Divya Rose; Geoffrey C. Waldbieser; Ethan Woodyard; Bradley M. Richardson; Esteban Soto; Cynthia B. Stine; Cynthia C. Ware; Paola Barato; Alvin C. Camus; Matt J. Griffin (Journal of Fish Diseases, 2026)
Edwardsiella anguillarum is a gram‐negative bacterium, synonymous with previously described atypical, fish‐pathogenic Edwardsiella tarda . Originally described from eels in 2015, E. anguillarum is an important global fish pathogen, particularly in tilapia. This study describes intraspecific phenotypic and genotypic variability among 17 E. anguillarum isolates from non‐anguillid fish hosts and varied geographic origins. Isolates demonstrated similar biochemical characteristics, with slight variation in motility and hydrogen sulfide production. Genomic relatedness among isolates was analysed with repetitive extragenic palindromic sequence‐based PCR (rep‐PCR) and multilocus sequence analysis (MLSA). Rep‐PCR with the ERIC II primer set revealed two distinct genetic clusters, while amplification strategies utilising the GTG 5 , BOX or ERIC I&II primer sets yielded more uniform profiles. While rep‐PCR deemed the isolates largely clonal, MLSA schemes using reference genes from published Edwardsiella MLSA studies revealed E. anguillarum isolates formed five discrete phylogroups. A unique, ~91.5 kB plasmid was identified in Costa Rican and Colombian isolates, associated with conjugative and transposable elements, plasmid mobilisation, and adhesion; however, no plasmid mediated antibiotic resistance genes were identified. This study provides insight into genetic diversity among E. anguillarum isolates from different hosts and geographic regions, identifying an optimal MLSA scheme from previous reports applicable to E. anguillarum isolates.

Systematic revision of the genus Orchidasma Looss, 1900 and description of Orchidasma orchilobata n. sp. from the loggerhead Caretta caretta (L.) and Kemp’s ridley Lepidochelys kempii (Garman) turtles - Thomas G. Rosser; Aiden Meaux; Ethan T. Woodyard; Justin M. Stilwell; Bradley M. Richardson; Logan R. S. Robison; Jill B. Hudnall; Kaylin McNulty; Jonah A. Nguyen; Divya Rose; Debra Moore; Beth Peterman; et al. (Systematic Parasitology, 2025)

Morphological and molecular data establishes Clinostomum dolichorchum n. sp. (Digenea: Clinostomidae) in the great blue heron Ardea herodias L. and American bullfrog Rana catesbeiana Shaw - Jonah A. Nguyen; Ethan T. Woodyard; Chris T. McAllister; Susan V. Marcquenski; Divya Rose; Celene M. Slifka; Logan R. S. Robison; Matt J. Griffin; T. Graham Rosser (Systematic Parasitology, 2024)

A comprehensive health effects assessment of the use of sanitizers and disinfectants during COVID-19 pandemic: a global survey - Fallah Hashemi; Lori Hoepner; Farahnaz Soleimani Hamidinejad; Daniela Haluza; Sima Afrashteh; Alireza Abbasi; Elma Omeragić; Belma Imamović; Narin A. Rasheed; Taqi M. J. Taher; Fitri Kurniasari; Dhuha Youssef Wazqar; et al. (Environmental Science and Pollution Research, 2023)